Studying and treating schizophrenia using virtual reality: a new paradigm. - Freeman, D (2008)
Understanding schizophrenia requires consideration of patients' interactions in the social world. Misinterpretation of other peoples' behavior is a key feature of persecutory ideation. The occurrence and intensity of hallucinations is affected by the social context. Negative symptoms such as anhedonia, asociality, and blunted affect reflect difficulties in social interactions. Withdrawal and avoidance of other people is frequent in schizophrenia, leading to isolation and rumination. The use of virtual reality (VR)--interactive immersive computer environments--allows one of the key variables in understanding psychosis, social environments, to be controlled, providing exciting applications to research and treatment. Seven applications of virtual social environments to schizophrenia are set out: symptom assessment, identification of symptom markers, establishment of predictive factors, tests of putative causal factors, investigation of the differential prediction of symptoms, determination of toxic elements in the environment, and development of treatment. The initial VR studies of persecutory ideation, which illustrate the ascription of personalities and mental states to virtual people, are highlighted. VR, suitably applied, holds great promise in furthering the understanding and treatment of psychosis.